The Lectin Pathway of Complement in Myocardial Ischemia/Reperfusion Injury—Review of Its Significance and the Potential Impact of Therapeutic Interference by C1 Esterase Inhibitor - Panagiotou, Anneza; Trendelenburg, Marten; Osthoff, Michael (Frontiers in Immunology, 2018)
Acute myocardial infarction (AMI) remains a leading cause of morbidity and mortality in modern medicine. Early reperfusion accomplished by primary percutaneous coronary intervention is pivotal for reducing myocardial damage in ST elevation AMI. However, restoration of coronary blood flow may paradoxically trigger cardiomyocyte death secondary to a reperfusion-induced inflammatory process, which may account for a significant proportion of the final infarct size. Unfortunately, recent human trials targeting myocardial ischemia/reperfusion (I/R) injury have yielded disappointing results. In experimental models of myocardial I/R injury, the complement system, and in particular the lectin pathway, have been identified as major contributors. In line with this, C1 esterase inhibitor (C1INH), the natural inhibitor of the lectin pathway, was shown to significantly ameliorate myocardial I/R injury. However, the hypothesis of a considerable augmentation of myocardial I/R injury by activation of the lectin pathway has not yet been confirmed in humans, which questions the efficacy of a therapeutic strategy solely aimed at the inhibition of the lectin pathway after human AMI. Thus, as C1INH is a multiple-action inhibitor targeting several pathways and mediators simultaneously in addition to the lectin pathway, such as the contact and coagulation system and tissue leukocyte infiltration, this may be considered as being advantageous over exclusive inhibition of the lectin pathway. In the present review, we summarize current concepts and evidence addressing the role of the lectin pathway as a potent mediator/modulator of myocardial I/R injury in animal models and in patients. In addition, we focus on the evidence and the potential advantages of using the natural inhibitor of the lectin pathway, C1INH, as a future therapeutic approach in AMI given its ability to interfere with several plasmatic cascades. Ameliorating myocardial I/R injury by targeting the complement system and other plasmatic cascades remains a valid option for future therapeutic interventions.